(untitled) (Rome, 2005)
This book brings together information on the contrasting characteristics, condition, present use and problems of the world's main natural grasslands. Since grassland is commercialized through the grazing animal, particular attention is paid to the livestock production systems associated with each main type. Grazing resources are more than simply edible herbage: many other factors have to be taken into account, notably water in all areas, and shelter in winter-cold climates. Seasonality of forage supply is a characteristic of almost all grazing lands, so the strategies for dealing with lean seasons are described. The main problems of each type are mentioned and possible strategies for their sustainable management discussed - taking into account their multiple functions, not only livestock production
Keywords: Grasslands,Đồng cỏ